Parenting and perinatal depression: meeting women's needs. (2nd October 2019) - Bhat, Amritha; Hoeft, Theresa; McCoy, Erin; Unutzer, Jurgen; Reed, Susan D.
Abstract: Introduction: Symptoms of depression during pregnancy and the postpartum period can negatively impact parenting. It is important to understand the parenting experiences of women with depression, and what parenting support they need. Methods: This is a mixed methods analysis of data (demographic data, depression outcomes, patient survey results, and transcripts of patient and care manager focus groups) from an open treatment trial of the feasibility of delivering perinatal depression treatment using collaborative care in a rural obstetric setting. Results: Patients who attended focus groups did not differ significantly from those who did not. Qualitative analysis of focus groups revealed the following themes: Maternal mood and parenting difficulties are interrelated; Access to depression treatment is complicated by expectations for the perinatal period and by factors related to parenting; Women want parenting support in the context of treatment for perinatal depression. Conclusion: Women receiving perinatal depression treatment experience unique parenting challenges and desire parenting support. Healthcare providers caring for these women should be mindful of their patients' parenting needs. Future research should explore ways to integrate parenting interventions with depression treatments. Mother–infant interaction is a key determinant of optimal infant development and integrating parenting support with perinatal depression treatments can have significant public health impact.